Popular economics : unpopular essays - Mahmud, Wahiduddin (Dhaka : The University Press Limited, 2002)
Collection of articles and commentaries written by the author for newspapers and occasional lectures delivered in popular forums, with reference to Bangladesh.
Includes bibliographical references and index.
Economics.
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Economic policy